PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, KOMPETENSI DAN KOMITMEN GURU TERHADAP KINERJA GURU SMK YADIKA SE-JAWA BARAT - Parlagutan Sinaga (Jurnal Satya Mandiri Manajemen dan Bisnis, 2025)
This study examines the influence of principal leadership, teacher competence, and teacher commitment on teacher performance at SMK Yadika in West Java. A quantitative descriptive method with a causality design was employed, collecting data from 74 permanent teachers out of a population of 240 using a validated Likert-scale questionnaire. Path analysis, multiple linear regression, and classical assumption tests were conducted using SPSS version 25. Results indicate that leadership, competence, and commitment significantly affect teacher performance both individually and collectively, explaining 58.7% of the variance (adjusted R-square = 0.587), with 41.3% attributed to unexamined factors. The novelty of this research lies in its focus on the Dual Learning System (PSG) in private vocational schools, emphasizing pedagogic competence in a regional context, differing from prior studies that targeted public schools or broader settings. These findings offer practical insights for enhancing vocational education quality and contribute to academic discourse on teacher performance in vocational education. Keywords : Principal leadership, teacher competence, teacher commitment, teacher performance.